Complementarities of HRM Practices - A Case for Employing Multiple Methods and Integrating Multiple Fields - Florian Englmaier; Katharina Schüßler (Center for Economic Studies and ifo Institute (CESifo), 2015)
We provide an overview over different literature streams that aim at explaining the origin of persistent productivity differences across organizations by variation in the use of management practices. We focus on human resource management (HRM) practices, document gaps in the literature, and show how insights from behavioral economics can inform the analysis. To this end, we develop a simple agency model illustrating how social preferences influence the design and impact of incentive schemes, investigate how auxiliary HRM practices can strengthen this interaction, and provide an overview over empirical investigations of this questions. Finally, we identify avenues for further research in this field.
Keywords: D22; M50; M52; 330; complementarities; HRM practices; method mix; social preferences; persistent productivity differences